2004
DOI: 10.1152/japplphysiol.00765.2003
|View full text |Cite
|
Sign up to set email alerts
|

PGC-1α mRNA expression is influenced by metabolic perturbation in exercising human skeletal muscle

Abstract: Endurance training leads to many adaptational changes in several tissues. In skeletal muscle, fatty acid usage is enhanced and mitochondrial content is increased. The exact molecular mechanisms regulating these functional and structural changes remain to be elucidated. Contractile activity-induced metabolic perturbation has repeatedly been shown to be important for the induction of mitochondrial biogenesis. Recent reports suggest that the peroxisome proliferator-activated receptor gamma coactivator 1alpha (PGC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

30
172
1
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(207 citation statements)
references
References 32 publications
30
172
1
4
Order By: Relevance
“…There is currently considerable interest in the role of PGC1 in numerous cellular functions, including mitochondrial biogenesis and lipid metabolism, and evidence is emerging linking muscle insulin resistance with mitochondrial dysfunction (Petersen et al 2003). Both acute (Baar et al 2002, Terada et al 2002, Pilegaard et al 2003, Norrbom et al 2004) and chronic (Goto et al 2000, Russell et al 2003, Short et al 2003, Terada & Tabata 2004) exercise increase PGC1 mRNA. In the present study we observed an 12-fold increase in PGC1 mRNA immediately following 3 h of cycle exercise in CON and have extended previous studies by demonstrating an 70% increase (P=0·09, n=5) of PGC1 protein content immediately after acute exercise.…”
Section: Discussionmentioning
confidence: 99%
“…There is currently considerable interest in the role of PGC1 in numerous cellular functions, including mitochondrial biogenesis and lipid metabolism, and evidence is emerging linking muscle insulin resistance with mitochondrial dysfunction (Petersen et al 2003). Both acute (Baar et al 2002, Terada et al 2002, Pilegaard et al 2003, Norrbom et al 2004) and chronic (Goto et al 2000, Russell et al 2003, Short et al 2003, Terada & Tabata 2004) exercise increase PGC1 mRNA. In the present study we observed an 12-fold increase in PGC1 mRNA immediately following 3 h of cycle exercise in CON and have extended previous studies by demonstrating an 70% increase (P=0·09, n=5) of PGC1 protein content immediately after acute exercise.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, an association with traits such as muscle fiber composition seems likely, as its transcriptional regulator PGC-1α has been suggested to show muscle fiber-specific expression, being associated with slow fibers in rodents (Lin et al 2002) and also in humans (Krämer et al 2006), though the latter remains controversial (Plomgaard et al 2006;Norrbom et al 2004). An association between FNDC5 expression and aerobic fibers has indeed been indicated in rodents (Wrann et al 2013;Roca-Rivada et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…PGC-1␣ is induced by exercise in skeletal muscle (e.g., refs. [15][16][17][18], and when expressed transgenically in skeletal muscle, it induces a switch in fibers toward more oxidative types I and IIa (19). PGC-1␣ is induced in the fasted liver, where it induces the mitochondrial beta oxidation of fatty acids and also stimulates the entire program of gluconeogenesis (20,21).…”
mentioning
confidence: 99%